Social change and the life course - Cohen, Gaynor (ed.) (London, Tavistock Publications, 1987)
A ife course approach is being seen as increasingly relevant within the social sciences. This book examines the family and social change from a life course perspective, faking account of life crises points such as leaving home or getting married, and analysing changes in personal identity, social status, and family relations. The contributors focus on relationships within the family, especially between the generations, and examine the different ways in which life course stages have been conceptualized. They stress the often overlooked fact that families evolve and change over time, making different demands on the economic and social system and, in furn, having different demands made on them. Social Change and the Life Course offers original perspectives on the relationship between the family and wider economic and political issues, showing how the family can be instrumental in bringing about changes in the structure of society. Demography, gender, social class, and ethnic origins are all considered in this wide-ranging and illuminating discussion of life course transitions and the dynamics of social change.
Keywords: Sociology